FUTUROLOGI DIASPORA PERANG DIPONEGORO TERHADAP NKRI DAN PENDIDIKAN ISLAM - Sidiq, Ngarifin; El Syam, Robingun Suyud; Haryanto, Sri (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2022)
The article aims to explore the futurology of Diponegoro's war diaspora against the Republic of Indonesia and Islamic education, emphasizing the possibility of the other side of the war. Using a historiographical approach to the futurological spectrum, research shows: that the Diponegoro war was actually a milestone in the archipelago's resistance to colonialism, unifying various elements of the nation, in the future sparking the struggle for Indonesian independence. On the other hand, this struggle was used as a means of preparing cadres for the clergy. After the arrest of the leader, the war diaspora spread to become the pioneers of establishing Islamic boarding schools or local religious leaders. Implications of research on the need to detail the pioneering pesantren of the Diponegoro war diaspora. These findings are expected to contribute to the development of Islamic education.